CD40L confers helper functions to human intra-melanoma class-I-restricted CD4+CD8+ double positive T cells. (1st December 2016) - Parrot, Tiphaine; Oger, Romain; Benlalam, Houssem; Raingeard de la Blétière, Diane; Jouand, Nicolas; Coutolleau, Anne; Preisser, Laurence; Khammari, Amir; Dréno, Brigitte; Guardiola, Philippe; Delneste, Yves; Labarrière, Nathalie; et al.
ABSTRACT: Although CD4 + CD8 + double positive (DP) T cells represent a small fraction of peripheral T lymphocytes in healthy human donors, their frequency is often increased under pathological conditions (in blood and targeted tissues). In solid cancers such as melanoma, we previously demonstrated an enrichment of tumor reactive CD4 low CD8 high αβ DP T cells among tumor-infiltrating lymphocytes of unknown function. Similarly to their single positive (SP) CD8 + counterparts, intra-melanoma DP T cells recognized melanoma cell lines in an HLA-class-I restricted context. However, they presented a poor cytotoxic activity but a strong production of diverse Th1 and Th2 cytokines. The aim of this study was to clearly define the role of intra-melanoma CD4 low CD8 high αβ DP T cells in the antitumor immune response. Based on a comparative transcriptome analysis between intra-melanoma SP CD4 +, SP CD8 + and DP autologous melanoma-infiltrating T-cell compartments, we evidenced an overexpression of the CD40L co-stimulatory molecule on activated DP T cells. We showed that, like SP CD4 + T cells, and through CD40L involvement, DP T cells are able to induce both proliferation and differentiation of B lymphocytes and maturation of functional DCs able to efficiently prime cytotoxic melanoma-specific CD8 T-cell responses. Taken together, these results highlight the helper potential of atypical DP T cells and their role in potentiating antitumor response.